2016
DOI: 10.1515/intag-2016-0013
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of N2O emissions from rapeseed cultivation in Poland by various approaches

Abstract: A b s t r a c t. The aim of this study was to compare four tools for calculation of nitrous oxide (N 2 O) emissions under the renewable energy directive. All the tools follow the methodology of the international panel on climate change. The first calculations of N 2 O fluxes were based on the Tier 1 method using the BioGrace tool. The second and the third ones followed the Tier 2 methodology, applying the global nitrous oxide calculator and the Lesschen emission factors, respectively. The last assessment was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In agriculture, the highest share (86%) in N 2 O emissions is that of the emissions from arable soils. A study by Syp et al (2016) showed that N 2 O emissions from cultivated soils in Poland varied within the range of 1.99-3.78 kg N 2 O ha/year. A reduction in these greenhouse gas emissions from agriculture can be achieved by: (i) large-scale implementation of precision farming; (ii) growing crops with a high carbon sequestration potential; (iii) organic fertilization; (iv) growing energy crops; (v) organic farming; (vi) afforestation of agricultural land (Sosulski et al 2017).…”
mentioning
confidence: 99%
“…In agriculture, the highest share (86%) in N 2 O emissions is that of the emissions from arable soils. A study by Syp et al (2016) showed that N 2 O emissions from cultivated soils in Poland varied within the range of 1.99-3.78 kg N 2 O ha/year. A reduction in these greenhouse gas emissions from agriculture can be achieved by: (i) large-scale implementation of precision farming; (ii) growing crops with a high carbon sequestration potential; (iii) organic fertilization; (iv) growing energy crops; (v) organic farming; (vi) afforestation of agricultural land (Sosulski et al 2017).…”
mentioning
confidence: 99%
“…The studies carried out so far of other authors [26,29,43,44] have indicated that taking local environmental conditions in the GNOC calculator used in this work into account allows for a more accurate estimation of field emission of N 2 O. It is usually lower than the emission estimated with the use of a simpler, but omitting local climatic conditions, soil, and farm management method, IPCC method at the Tier 1 level.…”
Section: Resultsmentioning
confidence: 85%
“…These data can only be collected by sampling at the farm scale [24]. The GNOC tool was developed based production data from the Food and Agriculture Organization of the United Nations (FAO) database and the input data that are necessary for performing the calculations include, among others, the place of cultivation, grain and straw yields, soil conditions, information on irrigation, the dose of applied fertilizers, information on post-harvest residues, as well as basic environmental parameters [25,26]. This tool calculates N 2 O emissions that are based on the approach of Stehfest and Bouwman [27].…”
Section: The Methodology For Assessment Ghg Emissions From Biomass Prmentioning
confidence: 99%
“…The tool was developed using production data from a United Nations Food and Agricultural Organisation (FAO) database. Input data include such factors as crop location, cereal and straw yield, soil conditions, irrigation, fertiliser dosage, residues, and basic environmental parameters [96,98]. This tool calculates N 2 O emissions that are based on the approach of Stehfest and Bouwman [99].…”
Section: Ghg Emissionmentioning
confidence: 99%